Defisiensi Strategi: Faktor Kegagalan Program Food Estate di Kalimantan Tengah Perspektif QS. Yusuf [12]: 54-58 - Khair, Muhammad Saiful; Lestari, Mega Asri; ., Syifa; El-Bilad, Cecep Zakarias (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
The food estate policy in Central Kalimantan has drawn controversy because it is considered to hurt the local community. However, if studied further, this policy has a good goal orientation. However, it is often thwarted by a clumsy management system. To overcome this, QS. Yusuf [12]: 54-58 provides a solution in the form of an excellent managerial system exemplified by Yusuf in facing the lean times. By using the thematic method in the data collection process and George R. Terry's management theory as an analytical tool, this article aims to determine the factors that caused the failure of the food estate program in several areas of Central Kalimantan with the reference point of Yusuf's story in QS. Yusuf [12]: 54-58. The results of the study showed that the failure of the food estate program in several areas in Central Kalimantan Province was due to the need for more mature planning by the Indonesian government. As a result, there was a series of reactions, namely the neglect of other management functions such as organizing, actuating, and controlling (as in George Robert Terry's theory), so the program could not run well.